Renal Support for Acute Kidney Injury in the Developing World - Annigeri, Rajeev A.; Ostermann, Marlies; Tolwani, Ashita; Vazquez-Rangel, Armando; Ponce, Daniela; Bagga, Arvind; Chakravarthi, Rajasekara; Mehta, Ravindra L. (Elsevier, 2017)
There is wide variation in the management of acute kidney injury (AKI) and the practice of renal replacement therapy (RRT) around the world. Clinicians in developing countries face additional challenges due to limited resources, reduced availability of trained staff and equipment, cultural and socioeconomic aspects, and administrative and governmental barriers. In this article, we report the consensus recommendations from the 18th Acute Dialysis Quality Initiative conference in Hyderabad, India. We provide the minimal requirements for provision of acute RRT in developing countries, including patient selection, choice of RRT modality and monitoring, transition, and termination of acute RRT. We also discuss areas of uncertainty and propose themes for future research. These recommendations can serve as a foundation for clinicians to implement renal support for AKI in low resource settings.
Keywords: acute kidney injury; CRRT; developing countries; dialysis; dose; IHD; modality; PD; renal support; resources; SLED